I'll give you the sun - Nelson, Jandy (New York : Dial Books, an imprint of Penguin Group (USA) LLC, 2014)
Jude and her twin brother, Noah, are incredibly close. At thirteen, isolated Noah draws constantly and is falling in love with the charismatic boy next door, while daredevil Jude cliff-dives and wears red-red lipstick and does the talking for both of them. But three years later, Jude and Noah are barely speaking. Something has happened to wreck the twins in different and dramatic ways... until Jude meets a cocky, broken, beautiful boy, as well as someone else -- an even more unpredictable new force in her life. The early years are Noah's story to tell. The later years are Jude's. What the twins don't realize is that they each have only half the story, and if they could just find their way back to one another, they'd have a chance to remake their world.
Young Adult.
Accelerated Reader
740
Reading Counts
Michael L. Printz Award, 2015.
Keywords: Twins -- Juvenile fiction; Teenage artists -- Juvenile fiction; Siblings -- Juvenile fiction; Mothers -- Death -- Juvenile fiction; Grief -- Juvenile fiction; Sibling rivalry -- Juvenile fiction; Miscommunication -- Juvenile fiction; Gay teenagers -- Juvenile fiction; Families -- Juvenile fiction; California -- Juvenile fiction; Artists -- Fiction; Twins -- Fiction; Brothers and sisters -- Fiction; Gay people -- Fiction; Grief -- Fiction; Death -- Fiction; Family life -- California -- Fiction; Michael L. Printz Award, 2015.; California -- Fiction; Michael L. Printz book award: Winner -- 2015.